Poland Energy Transition : The Path to Sustainability in the Electricity and Heating Sector - World Bank Group (World Bank, Washington, DC, 2018)
This report explores options to scale up and accelerate the energy transition to cleaner electricity and district heating generation mixes and reconcile the government’s concerns over the serious local air pollution and commitments to combat climate change. The report draws three main conclusions from the analyses and consultations carried out during the last six months: Despite impressive progress towards sustainability, Poland’s coal-dominated energy sector imposes heavy health costs on its population. A recent World Bank report estimated that the cost of ambient air pollution amounts to about USD 31-40 billion, equivalent to 6.4-8.3 percent of GDP in 2016. Moreover, deterioration of ambient air quality is responsible for a significant health burden with an estimated 44,500 premature deaths per year. The ambitious cleaner strategy to scale up renewable energy sources in the power and district heating generation mix is economically justified, if local and global environmental benefits are accounted for. Poland is moving in the right direction on energy transition with its envisioned targets on renewable energy, but achieving the more ambitious targets under the European Union Emission Trading Scheme requires intensified efforts to scale up and accelerate the penetration of clean energy. Active labor market policies can help mitigate employment impacts, which are expected to be negligible at national level and modest at local level given a dynamic economy and tight labor.